Factors influencing consumer’s retail formats choice for fresh fruits purchase in Klang Valley Malaysia - Gindi, Abdullahi Auwal; Abdullah, Amin Mahir; Ismail, Mohd Mansor; Mohd Nawi, Nolila (Academia Scholarly Journals, 2016)
This study attempts to identify attributes or factors influencing consumers’ retail formats choice in fresh fruits (FF) purchase. The study covered consumers in Klang Valley area, Malaysia and period of the study is between June to December 2014. Seven hundred (700) respondents were randomly selected using multi- stage cluster sampling technique. The demographic characteristics result of the respondents includes their educational level, income level and their marital status. The product attributes considered most important by the fresh fruits consumers are level of ripening (72%), size and shape of the fruit (65%) and color of the fruits (63%). Freshness, safety of the product and product quality are the three factors yielded from the factor analysis. Likewise, convenience, entertainment and services offered are the retail formats attributes considered by the fresh fruits consumers. From the regression results it was observed that all the estimated factors have significant effect on frequency of visit to the traditional formats. However, only quality and entertainment were the significant factors affecting patronage of modern retail formats. The finding of this research will help the retail formats managers and policy makers identify the salient issues to be considered in fresh fruits marketing strategies.